Determinants of economic growth In Kenya - Kaara, Hellen Njeri (Strathmore University, 2015)
Economic growth has been a major issue in the world today especially in developing countries. This study examines the determinants of economic growth in Kenya the period 1971-20 II with a particular focus on interest rates, savings and inflation rates . The aim of the study is to determine the causality between interest rates, inflation, savings and economic growth, and the extent to which each of the determinants affect economic growth. Johansen co-integration shall be used test to check for long term relationship between the identified variables, granger causality test to determine granger causality among the different variables and impulse response test to determine how shocks in the one variable affect the other variables. The results show a unidirectional causality from interest rates, inflation and savings to GOP per capita. The impulse response test revealed that shocks in inflation have a negative effect on GOP per capital in the short run while shocks in savings have a positive effect in the sholi run. Shocks in interest rates were found to have a constant effect in the short run. However, shock effects take long to die off in in the three instances. From the findings, it is recommended that relevant policies should be formulated to ensure that each of this factors move in a direction such that they enhance economic growth.